Influence of cavitation on the acoustic boundary conditions in water hammer experiments. Issue 1 (May 2021) - Klein, Sebastian; Traudt, Tobias; Oschwald, Michael
Abstract: A water hammer event is created by stopping a flow in a pipeline using a fast closing valve. The pressure is measured at three different positions upstream the valve. Cavitation occurs close to the valve and is detected by vapour pressure in the pipeline. Frequencies in the liquid part of the pipe were measured and statistically evaluated in order to analyse whether cavitation acts as a boundary condition of acoustics. Without cavitation one side of the pipe is an open end, while the other side is a closed end. In presence of cavitation the cavity should act like an open end due to the high change of acoustic impedance from liquid to gaseous phase. Therefore it is expected that the oscillating behavior is changing from an open/close to an open/open system. The measured frequencies indeed show a change towards an open/open configuration. It is shown that cavitation acts as a boundary condition in this system.